Inverse Cherenkov dielectric laser accelerator for ultra-relativistic particles. (26th January 2023) - Zhang, Liwen; Liu, Weihao; Liu, Yucheng; Jia, Qika; Sun, Baogen; Xu, Hongliang; Liu, Shengguang
Abstract: Recently, the laser-driven dielectric particle accelerator based on the inverse Cherenkov effect has aroused great interest, because it provides an option for developing desktop or even on-chip particle accelerators. So far, only sub-relativistic cases have been investigated. Previous studies showed that when the particle velocity reaches ultra-relativistic range, the acceleration gradient of an inverse Cherenkov laser-driven dielectric accelerator with a single-side dielectric structure drops sharply. Here we illustrate that, by using a double-sided dielectric structure, a high acceleration gradient for ultra-relativistic particles can still be obtained. In addition, we find that, in the ultra-relativistic region, the acceleration gradient increases (not decreases) with the increase of particle energy. The single-sided and double-sided accelerator models under unilateral and bilateral laser-driven conditions are investigated in detail. The results obtained are important for developing an inverse Cherenkov laser-driven dielectric accelerator for both sub-relativistic and ultra-relativistic regions.